Desarrollo de un programa informático para estudios nutricionales. - Defagó, María D.; Perovic, Nilda R.; Aguinaldo, Cristina A.; Actis, Adriana B. (Pan American Journal of Public Health / Revista Panamericana de Salud Pública, 2009)
The Interfood v. 1.3 software program was developed to process nutrition information and generate data on dietary intakes-in terms of food, nutrients, and phytochemical substances-valid for conducting studies on nutrition and epidemiology. The program has three basic components: the dietary intake frequency questionnaire CFCA); a database of common foods and their composition of 131 possible substances (macro- and micronutrients and phytochemicals); and a relational database that links the CFCA data with the food database. In this manner, the Interfood software program calculates the amount of food, nutrients, and phytochemical substances consumed by an individual daily, weekly, and monthly. Interfood is an open-source program; as such, the database can be modified and updated according to study requirements. This program has already proven useful to various studies of nutrition and epidemiology.